Pelatihan Bahasa Inggris Melalui Metode Silent Way Untuk Meningkatkan Kosa Kata Perawat Dalam Kemampuan Berbicara Bahasa Inggris Di Rumah Sakit - Devi Annisa Marpaung; Yusnika Damayanti; Yusnaini Yusnaini; Nurhasanah Nurhasanah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The silent way English language training was carried out at the Nurul Hasanah Kutacane Hospital. This silent way English language training aims to improve basic English skills for hospital employees. This English training method uses the silent way method. English language training using the silent method is used so that hospital employees can practice English language skills in medical sciences that will be used in the world of work. This English language training using the silent method was carried out thanks to collaboration between Nurul Hasanah Kutacane University and Nurul Hasanah Kutacane Hospital. This English language training is to assess evaluation using Quasy-Experiment (pre-experimental designs) with a design using one group pretest-posttest, where in this design there is no comparison group (control), but the first observation (pretest) has been carried out which allows the team to examine changes that occur after an experiment or posttest. The results obtained by the community service team showed significant changes in English language training through the silent way method to increase nurses' vocabulary in speaking English in hospitals.